Exotic phases of matter in compact stars - Sandin, Fredrik (Luleå tekniska universitet, Materialvetenskap, 2007)
This doctoral thesis in physics at Luleå University of Technology is devoted to the phenomenology of compact stars, and theoretical models of their interior. Particle physics has provided fundamental concepts and details needed to develop a description of matter and the evolution of the universe. It is, however, difficult to obtain information about the properties of matter at low temperature and high density from such experiments. In this context, astrophysical observations constitute an important source of information, thanks to the high resolution of present and near-future terrestrial and space-based observatories. The density of matter in neutron stars exceeds that in atomic nuclei, and little is known about the nature of their interior. It is clear that the interaction between the smallest observed building blocks of atomic nuclei, the quarks, becomes weaker with increasing density. Matter should therefore dissolve into a state of nearly free quarks at high densities, and models of classical superconductivity advocate that this state is a superconductor. The argument for this is simple: a low-temperature Fermi system with a weak attractive interaction is unstable with respect to formation of Cooper pairs. It is not known if this state of matter exists in neutron stars, but models suggest that it is possible. The major part of the work summarised in this thesis is the development of a model of superconducting quark matter, and its consequences for the phenomenology of neutron stars and their formation in the collapse of massive stars. It is a Nambu - Jona-Lasinio model with self-consistently calculated quark masses and pairing gaps, which properly accounts for the beta-equilibrium and/or charge neutrality constraints in compact stars and heavy-ion collisions. Phase diagrams and equations of state of superconducting quark matter are presented, and the influence of different assumptions about the effective quark interaction is investigated. The effect of neutrino untrapping in hypothetical quark cores of ...